The Effect of Corporate Governance on Auditor-Client Realignments - Cassell, Cory A.; Giroux, Gary A.; Myers, Linda A.; Omer, Thomas C. (Auditing : a journal of practice and theory, 2012)
Events leading up to the implementation of the Sarbanes-Oxley Act of 2002 (SOX) increased the public's focus on corporate governance and increased regulatory scrutiny of corporate governance mechanisms. These events also contributed to a massive restructuring in the audit market that resulted in the transfer of a large number of clients from Big N to non-Big N audit firms. We extend prior research examining the determinants of auditor-client realignments by investigating the effect of corporate governance on downward (i.e., from Big N to non-Big N auditors) switching activity. We develop a corporate governance index comprised of governance characteristics that we expect auditors to find more desirable in their clients (specifically, board and audit committee independence, diligence, and expertise). The results suggest that Big N auditors consider client corporate governance mechanisms when making client portfolio decisions. Specifically, downward auditor-client realignments are more likely for clients that score lower on our corporate governance index. However, the influence of audit committee-related corporate governance components on downward auditor-client realignments decreased post-SOX. The reduced effect of audit committee-related corporate governance components is consistent with what would be expected if the audit committee-related rules imposed by SOX reduced the variation in audit committee quality across clients. Data Availability: The data used are publicly available from the sources cited in the text.